INDIGENOUS WOMEN IN THE DRAFT LAW OF INDIGENOUS PEOPLES: AN APPROACH BASED ON LEGAL NEUTRALITY AND PANCASILA VALUES - Rika Saraswati (Faculty of Law, Universitas Diponegoro, 2025)
The Draft Law on Indigenous Peoples’ Affairs in Indonesia has sparked significant debate, particularly concerning the protection and recognition of Indigenous women's rights. Indigenous Peoples in Indonesia have long maintained distinct socio-cultural identities, yet continue to face legal challenges, exacerbated by overlapping regulations that often neglect or inadequately address their specific needs, especially the rights of Indigenous women. Although the Indonesian Constitution recognises Indigenous Peoples, the enforcement of their rights remains inconsistent, particularly regarding gender equality. This research compares two versions of the draft law: one proposed by the Indonesian House of Representatives (DPR) and another drafted by Indigenous Peoples and their coalitions. While both versions aim to recognise Indigenous Peoples legally, they differ significantly in their treatment of Indigenous women’s rights. The DPR’s version fails to adequately address gender equality or the collective rights of Indigenous women. In contrast, the Indigenous Peoples’ version explicitly acknowledges their rights, particularly regarding land and natural resource management. The research highlights the double marginalisation faced by Indigenous women—both within their communities and in broader societal structures. Patriarchal values within Indigenous communities and the state often exclude women from decision-making processes, leaving them vulnerable to violence, poverty, and further marginalisation. The study argues that gender equality must be a core component of the legal framework to empower Indigenous women, ensuring they are recognised as equal participants in their communities and have legal protection to manage their lands and cultural practices. The comparative analysis suggests that the Indigenous Peoples’ version aligns more closely with international human rights standards, especially regarding gender equality. However, challenges remain, such as the exclusion of women from customary decision-making bodies. This research calls for a legal framework that fully incorporates gender equality into Indigenous rights, reflecting the Pancasila values of equality, social justice, and respect for diversity, and ensuring the recognition of Indigenous women as key stakeholders in the preservation of their heritage and rights.